Rural Development in Haryana: Problems, Prospects and Measures for Sustainable Development - Singh, Gurcharan (Gyan Management Journal, 2015)
Rural development has assumed global attention especially among the developing nations. It has great significance for a country like India where majority of the population live in rural areas.The present study is conducted with an aim to highlight the problems and prospects in the sustainable rural development in Haryana. For the purposes, the study used a mixed method approach for investigation. It included review of secondary data sources like earlier research work, published and unpublished government documents such as Five year plans, various reports etc. To bring more clarity on the research area researcher contacted the locals residents of rural areas, government offices & NGOs and other stakeholders associated in rural development activities in the Haryana. The result of the research depicted that number of schemes &programs were started in Haryana for the development of rural area. But, even after introducing various ways of good measures to improve the living standard of rural inhabitants; the success is not achieved due to poor administration and poor coordinated governance. On the basis of the study several recommendations were also forwarded; if strictly adhere ta may lead to drastic improvement in the rural development